Survival analysis and prognostic factor of non-Hodgkin lymphoma treated in Hospital Universiti Sains Malaysia (HUSM) - Che Soh, Nur Sabrina; Bachok, NorSa'adah; Baba, Aziz; Wan Muhammad, Wan Mohd Zahiruddin (2011)
INTRODUCTION: Non-Hodgkin’s lymphoma (NHL) is included in the ten leading cancers worldwide, accounting for an estimated more than 63 thousand new cases and over 19 thousands deaths per year. The study on survival rate and prognostic factors may be useful in building a better intervention program as well as improving survival rate.